2020
DOI: 10.1111/ctr.14042
|View full text |Cite
|
Sign up to set email alerts
|

Heart transplantation in the early phase of the COVID‐19 pandemic: A single‐center case series

Abstract: On February 26, 2020, the first case of community spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the United States (US) was confirmed. 1 SARS-CoV-2 causes coronavirus disease 2019 (COVID-19), and on March 11, the World Health Organization declared COVID-19 a global pandemic. By May 27, 2020, SARS-CoV-2 had infected over 1.6 million people in the United States, resulting in over 100 000 deaths. 2 The ongoing pandemic has presented a challenging predicament for organ transplantation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…As a result, some transplant centers have been forced to decrease their ability to offer transplantation in the midst of the pandemic. This has resulted in an overall decrease in the number of transplants performed in the United States coupled with an increased number of inactive patients on the UNOS waiting list 1 …”
Section: Introductionmentioning
confidence: 99%
“…As a result, some transplant centers have been forced to decrease their ability to offer transplantation in the midst of the pandemic. This has resulted in an overall decrease in the number of transplants performed in the United States coupled with an increased number of inactive patients on the UNOS waiting list 1 …”
Section: Introductionmentioning
confidence: 99%
“…This triple therapy regimen was also utilized by centers in prior case series that showed favorable outcomes in the early postoperative period for patients transplanted at the start of the pandemic. 5,6 Therefore, we expected to have similar 1-year freedom from any treated rejection, acute antibody mediated rejection, and acute cellular rejection between the two groups which was seen in the current study. And although patients were transitioned to video visits after postoperative month 6, at home blood draws were conducted to adjust immunosuppression dosages accordingly and further help prevent rejection.…”
Section: Discussionmentioning
confidence: 58%
“…An 87-patient study in China reported post-transplant patients experiencing virus-related morbidities comparable to those in the general population. [4][5][6] In our study, one patient was transiently seropositive at two months posttransplant but was asymptomatic throughout the following eight months. This suggests that patients transplanted during the pandemic may be at no greater risk than the general population throughout their perioperative course.…”
mentioning
confidence: 49%
“…Under similar conditions, Hsu et alin Los Angeles performed eight successful heart transplants at the University of California early in the pandemic. 4 Regarding donor-to-recipient transmission risk, donor institutions confirmed SARS-CoV-2 negativity in both cases. Organ procurement was limited to single surgeon/restricted geographic radius.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation